2020
DOI: 10.1155/2020/7147498
|View full text |Cite
|
Sign up to set email alerts
|

Musa balbisiana Fruit Rich in Polyphenols Attenuates Isoproterenol-Induced Cardiac Hypertrophy in Rats via Inhibition of Inflammation and Oxidative Stress

Abstract: Musa balbisiana Colla (Family: Musaceae), commonly known as banana and native to India and other parts of Asia, is very rich in nutritional value and has strong antioxidant potential. In the present study, we have developed Musa balbisiana (MB) fruit pulp powder and evaluated its cardioprotective effect in cardiac hypertrophy, which is often associated with inflammation and oxidative stress. An ultra-high-pressure liquid chromatography-mass spectrometer (UPLC-MS/MS) has been used for the detection and systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…The inhibitory effects induced by the garlic hydroalcoholic extract on 8-iso-PGF 2α levels could be related to its phenolic acid and flavonoid content, with particular regard to the levels of protocatechuic acid and gallic acid [ 41 , 51 , 52 , 53 , 54 ]. In this context, polyphenol compounds were found to be able to exert cardioprotective effects through the inhibition of oxidative stress and inflammation [ 55 , 56 , 57 , 58 , 59 ]. In particular, it has been demonstrated that protocatechuic acid, one of the main secondary metabolites of garlic, exhibits antioxidant and anti-inflammatory effects [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory effects induced by the garlic hydroalcoholic extract on 8-iso-PGF 2α levels could be related to its phenolic acid and flavonoid content, with particular regard to the levels of protocatechuic acid and gallic acid [ 41 , 51 , 52 , 53 , 54 ]. In this context, polyphenol compounds were found to be able to exert cardioprotective effects through the inhibition of oxidative stress and inflammation [ 55 , 56 , 57 , 58 , 59 ]. In particular, it has been demonstrated that protocatechuic acid, one of the main secondary metabolites of garlic, exhibits antioxidant and anti-inflammatory effects [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, several naturally occurring compounds have been shown to alleviate the hypertrophic phenotype through suppression of oxidative stress. For instance, the pulp powder extracted from Musa balbisiana (banana) [90], the lowbush blueberry extract (Vaccinium angustifolium) [91], the aqueous extract of the Terminalia arjuna bark [92] and pomegranate juice [93] have been associated with reduction in heart weight, fibrosis, inflammation and oxidative stress. In addition to supressing cardiac hypertrophy, these compounds have been reported to exert beneficial effects across several pathologies suggestive of pleiotropic function.…”
Section: Therapeutic Strategies For Attenuating Oxidative Stress Anti...mentioning
confidence: 99%
“…It also did not indicate the type of the extract used. An elevation in oxidative stress and inflammation has been reported in isoproterenol-induced myocardial injury ( Kumari et al, 2020 ; Younis et al, 2020 ). Therefore, the extract most likely elicits protective effects through its antioxidant and anti-inflammatory properties, as previously reported ( Tewtrakul et al, 2015 ; Suwan et al, 2018 ).…”
Section: Effects On Myocardial Injurymentioning
confidence: 99%